PERAN KEPEMIMPINAN DAN KUALITAS KEHIDUPAN KERJA (QWL) DIMODERASI LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA (Studi kasus di SMK Negeri Kabupaten Jepara) - 11.52.02.0133, Aji Laksana (Jurnal Mahasiswa Pasca Sarjana, 2013)
The research aims to analyze the Leadership and Influence Quality of work life (QWL) moderated the job satisfaction working environment. research method used is descriptive quantitative, seeking independent variables affect the dependent variable. Primary data obtained from the survey questionnaire as a data collection tool, the secondary data obtained through oral information from school that the object of research. Regression test results indicate that the independent variables, which are not significant leadership on satisfaction, quality of work life (QWL) is significant to job satisfaction, whereas work environment affect the job satisfaction. interaction regression test data, we can conclude that the work environment can not be used as a moderator variable for leadership and quality of work life (QWL) on job satisfaction. Keywords: Leadership, Quality of work life (QWL), Work Environment and Job Satisfaction